2019
DOI: 10.1108/jm2-01-2019-0028
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming managers’ myopic decisions in a waste collection company

Abstract: Purpose The purpose of this paper is to show how the changing interrelationships between fleet management, human resources and outsourcer capacity areas are likely to counterbalance managerial policies, thereby generating a performance decay. The use of system dynamics modelling in a waste collection company offered an effective contribution to support decision makers to overcoming myopic decisions. Design/methodology/approach Literature review and a case study analysis (including interviews with company act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Simulation using system dynamics has also been used to investigate problems involving multifaceted elements that interact and evolve over time, as found in Total Productive Maintenance (TPM) [34], or by showing how changing interrelationships between fleet management, human resources and subcontractor capability areas are likely to counteract management policies, thus generating performance deterioration [35].…”
Section: Consultation and Analysis Of The Literaturementioning
confidence: 99%
“…Simulation using system dynamics has also been used to investigate problems involving multifaceted elements that interact and evolve over time, as found in Total Productive Maintenance (TPM) [34], or by showing how changing interrelationships between fleet management, human resources and subcontractor capability areas are likely to counteract management policies, thus generating performance deterioration [35].…”
Section: Consultation and Analysis Of The Literaturementioning
confidence: 99%
“…Bivona et al (2019) showed how the changing interrelationships between fleet management, human resources and outsourcer capacity areas are likely to counterbalance managerial policies, thereby generating a performance decay. The authors learned these lessons through a case study with a waste collection company where they made an effective contribution to support decision makers to overcoming their myopic decisions.…”
Section: Editorial For Special Issue “System Dynamics Contributions To Modelling In Management”mentioning
confidence: 99%
“…This is in contrast with the approach that offers solutions to customers by optimising the operations of the individual parts of an organisation without considering the way in which they interact (Martinez Garcia and Martínez Caro, 2009;Hsieh and Yuan, 2010). But there is more than that: System Dynamics could enable managers to develop more accurate cognitive representations about their business models (Moellers et al, 2019); or it could help managers to overcome decisional myopia, shifting the focus of their decision process from a single department to the whole business system (Bivona et al, 2019). Moreover, System Dynamics could be an important support tool for project management planning and monitoring activities (Li et al, 2009;Yujing et al, 2015).…”
Section: Understanding and Learning System Dynamicsmentioning
confidence: 99%